Genetic deletion of NMDA receptors suppresses GABAergic synaptic transmission in two distinct types of central neurons - Gu, Xinglong (Neurosci Lett, 2018)
NMDA-type ionotropic glutamate receptors (NMDARs) play an important role in the regulation of synapse development and function in the brain. Recently we have shown that NMDARs are critical for GABAergic synapse development in developing hippocampal neurons. However, it remains unclear whether NMDARs are important for establishment of GABAergic synaptic transmission in other types of neurons in the brain. Here we report that in both cortical pyramidal neurons and midbrain dopamine neurons in ventral tegmental area (VTA), genetic deletion of the GluN1 subunit, which is required for assembly of functional NMDARs, leads to a strong reduction of GABAergic synaptic transmission. These data demonstrate that NMDARs play an important role in the development of GABAergic synaptic transmission in two types of neurons with distinct developmental origins, and suggest that NMDARs are commonly involved in development of GABAergic synaptic transmission in different types of neurons in the brain.